2018
DOI: 10.1177/1359105318772073
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs and quality of life in multiple myeloma patients

Abstract: This cross-sectional study analysed the contributors and moderators of quality of life. The sample comprised 124 Portuguese multiple myeloma patients assessed on social support, spirituality, unmet needs, psychological morbidity and quality-of-life measures. Results showed that being older and a woman, as well as psychological morbidity and unmet emotional needs were significant predictors of worse quality of life as measured by the QLQ-C30. Unmet financial needs moderated the relationship between psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
(121 reference statements)
1
8
0
Order By: Relevance
“…Emotional support was also positively associated with SWL in our study. This is in line with a multitude of studies linking this type of support to increases in QoL (Bogart & Hemmesch, 2016; Ethgen et al, 2004; Pereira et al, 2018; Yao et al, 2015). Emotional support is thought to help restore one’s self-esteem and feelings of personal inadequacy by communicating that the chronically ill individual is loved and valued.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Emotional support was also positively associated with SWL in our study. This is in line with a multitude of studies linking this type of support to increases in QoL (Bogart & Hemmesch, 2016; Ethgen et al, 2004; Pereira et al, 2018; Yao et al, 2015). Emotional support is thought to help restore one’s self-esteem and feelings of personal inadequacy by communicating that the chronically ill individual is loved and valued.…”
Section: Discussionsupporting
confidence: 87%
“…Controls that were considered for both models were those found to be consistently important across multiple studies. These included gender, age, years since diagnosis, and both duration and severity of symptoms (Bogart & Irvin, 2017; Bosworth et al, 2000; Delgado, 2007; Ethgen et al, 2004; Grady et al, 1995; Kornblith et al, 2001; Pakenham, 1999; Pereira et al, 2018). Zero-order correlations were calculated for descriptive purposes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous cross-sectional registry study showed that adults with MM experienced significantly worse QoL compared to other cancers [41]. Factors associated with poor QoL include being older, female gender, financial stressors, psychological morbidity, and low physical activity [42][43][44]. In comparison to these cross-sectional studies which only capture information at one specific time point, our study used longitudinal assessment of QoL over a period of 6-months to show that most patients in fact improved or remained stable over time.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, transplant patients have different care needs after surgery (Been‐Dahmen et al, 2018; Forsberg et al, 2016). Unmet patients' needs are related to poor health status, increased depression or anxiety, and low quality of life (Forsberg et al, 2016; Pereira et al, 2018); hence, a reliable instrument must be routinely used to assess the unmet needs of patients after transplantation. However, no needs assessment scale is available for transplant recipients in current practice settings.…”
Section: Introductionmentioning
confidence: 99%